Concept of theatricality in the interpretation of the postmodern novel - Filimonova, A.P.; Kharitonova, L.M.; Sonmez, M.J.M. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article some problems of studying theatricality in the novel resulted from ambiguity of the term and the elusiveness of its possible theoretical implications are considered. It presents a cultural background to reveal the essential cultural nature of the phenomenon of theatre that causes the ambiguity and elusiveness of the concept. In this respect the article presents a discussion on the main features of theatricality attributed to it throughout different cultural periods. It concludes that the postmodern novel provides the most suitable material for studying theatricality in non-dramatic genres. Having studied the researches of theatrical semiotics, the author has concluded that they are to be considered as a way to avoid elusiveness of the term and to define it more precisely as a concept of the literature criticism. This discussion is channeled towards an understanding of which features of theatricality could be most useful in analyzing theatricality in novels. On this ground, it argues that the concept of theatricality in a literary text involves two main aspects: the structure of the chronotope and that of the character in the novel.
Постмодернистік романның интерпретациясындағы театрлану концептісі
Концепт театральности в интерпретации постмодернистского романа
Keywords: theatricality; postmodernism; theatrical semiotics; chronotope